STATISTICAL RESEARCH IN EVOLUTIONARY GENETIC RELATIONSHIP OF DMS-, DW-, KW- AND KE-TYPES OF DOUBLE STARS - Dryomova, G. N.; Svechnikov, M. A. (Одеські астрономічні публікації, 2017)
Statistical relations as spectrum-period, mass of primary component-semi-major axes of an orbit, excesses of luminosity and radius-mass of component, Karetnikov's diagram, modern and initial distributions of the binaries in the 1 ps3 of Sun neighbourhood allow to solve the problem of evolutionary relationship for close binary systems and describe conditions at which evolutionary transitions such as DMS -> DW -> KW <- KE take place.